2019
DOI: 10.1177/0894845319847288
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Indirect Effects of Self-Concept on Work Readiness Through Resilience and Career Calling

Abstract: The current study examined the relations among self-concept, career calling, resilience, and work readiness in a Malaysian sample of vocational college students ( N = 674). As hypothesized, self-concept was positively associated with work readiness. To explain this relation further, we examined the indirect effect of self-concept through calling and resilience on work readiness. Using structural equation modeling, both career calling and resilience were found to be significant avenues through which self-concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
(50 reference statements)
0
17
0
2
Order By: Relevance
“…The managers or HR practitioners can facilitate a supportive climate by opening up a discussion about their employees or clients' understanding of their calling and the factors that might influence the emergence of their calling. HR practitioners might employ an assessment using Meaning of Life Questionnaire (MLQ) to facilitate discussion and to determine if the clients have formulated or have been seeking meaning which is an integral component of calling, later the practitioners can aid their clients in guiding them to find their calling in their job (Adams, 2012;Lau et al, 2020). Our findings show the importance of proactivity for employees and organizations.…”
Section: Conclusion Limitation and Suggestionmentioning
confidence: 83%
“…The managers or HR practitioners can facilitate a supportive climate by opening up a discussion about their employees or clients' understanding of their calling and the factors that might influence the emergence of their calling. HR practitioners might employ an assessment using Meaning of Life Questionnaire (MLQ) to facilitate discussion and to determine if the clients have formulated or have been seeking meaning which is an integral component of calling, later the practitioners can aid their clients in guiding them to find their calling in their job (Adams, 2012;Lau et al, 2020). Our findings show the importance of proactivity for employees and organizations.…”
Section: Conclusion Limitation and Suggestionmentioning
confidence: 83%
“…Of the personal factors that the extant literature has found to play a role in connecting individuals to their calling, or helping them to manifest it more fully, being proactive and tenacious (French & Domene, 2010 ; Jaffery & Abid, 2020 ), resiliency (French & Domene, 2010 ; Rojas, 2017 ), personal agency (Bandura, 1991 ; Elangovan et al, 2010 ), core self-evaluations (Hirschi & Herrmann, 2012 ), clear sense of identity (Dalla Rosa et al, 2019 ; French & Domene, 2010 ; Lau et al, 2020 ), personal trauma or adversity (Cremen, 2019 ; Duffy et al, 2012b ; Haney‐Loehlein et al, 2015 ; Hernandez et al, 2011 ; Rojas, 2017 ), fit with others with similar orientations (Dobrow, 2013 ), changes in one’s self or life circumstances (Billett, 2011 ; Coulson et al, 2012 ; Dewey, 1990 ; Hankle, 2009 ; Vianello et al, 2020 ), personal reflection or exploration (Bott & Duffy, 2015 ; Duffy et al, 2012b ; Haney‐Loehlein et al, 2015 ; Hernandez et al, 2011 ), search for life meaning (Elangovan et al, 2010 ), dysfunctional career thoughts (Galles & Lenz, 2013 ), career maturity (Duffy et al, 2011 ), and life history (Billett, 2011 ; Haney‐Loehlein et al, 2015 ) were identified as being enablers to a lived calling in this study, albeit to varying degrees. For example, tenaciousness as reflected in the code label ‘Determination’ was cited eleven times, whereas the theme of resiliency, as captured by code label ‘Ability to deal with real/perceived failure’ was cited only once by respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The personal factors that have been found to play a role in connecting people to their calling, or helping them to manifest it more fully, were identified by the following studies: being proactive and tenacious (French & Domene, 2010 ; Jaffery & Abid, 2020 ), resiliency (French & Domene, 2010 ; Rojas, 2017 ), personal agency (Bandura, 1991 ; Elangovan et al, 2010 ), core self-evaluations (Hirschi & Herrmann, 2012 ), clear sense of identity (Dalla Rosa et al, 2019 ; French & Domene, 2010 ; Lau et al, 2020 ), personal trauma or adversity, e.g. a midlife crisis (Cremen, 2019 ; Duffy et al, 2012b ; Haney-Loehlein et al, 2015 ; Hernandez et al, 2011 ; Rojas, 2017 ), fit with others with similar orientations (Dobrow, 2013 ), changes in one’s self or life circumstances, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While resilience may be considered an -experience‖ (Madrid, Diaz, Leka, Leiva, & Barros, 2018, p. 465), the term is usually defined as -the human ability to adapt in the face of tragedy, trauma, adversity, hardship, and ongoing significant life stressors‖ (Newman, 2005, p. 227). Notably, in the context of positive adaptation to stressful events and adversity, the concept has been researched extensively in the literature (e.g., American Psychological Association, 2014; Britt, Shenn, Sinclair, Grossman & Klieger, 2016;Fikretoglu & McCreary, 2012;Lau, Wilkins-Yel, & Wong, 2020;Meredith et al, 2011;Oshio, Taku, Hirano, & Saeed, 2018).…”
Section: Resiliencementioning
confidence: 99%